2012
DOI: 10.1242/dev.079525
|View full text |Cite
|
Sign up to set email alerts
|

Formation and specification of a Drosophila dopaminergic precursor cell

Abstract: Dopaminergic neurons play important roles in animal behavior, including motivation, reward and locomotion. The Drosophila dopaminergic H-cell interneuron is an attractive system for studying the genetics of neural development because analysis is focused on a single neuronal cell type. Here we provide a mechanistic understanding of how MP3, the precursor to the H-cell, forms and acquires its identity. We show that the gooseberry/gooseberry-neuro (gsb/gsb-n) transcription factor genes act to specify MP3 cell fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Midline cell expression of a gene is particularly easy to identify due to the characteristic midline stripe of embryonic expression. The development of the midline cells is well understood, with many of the key regulatory proteins identified (Thomas et al, 1988; Watson et al, 2011; Watson and Crews, 2012; Wheeler et al, 2008). In particular, the Drosophila single-minded (sim) gene, which encodes a bHLH-PAS transcription factor, controls early development of the CNS midline cells (Nambu et al, 1991) by acting as a transcriptional activator that promotes the midline transcriptional program (Nambu et al, 1990) and indirectly represses the lateral CNS program (Estes et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Midline cell expression of a gene is particularly easy to identify due to the characteristic midline stripe of embryonic expression. The development of the midline cells is well understood, with many of the key regulatory proteins identified (Thomas et al, 1988; Watson et al, 2011; Watson and Crews, 2012; Wheeler et al, 2008). In particular, the Drosophila single-minded (sim) gene, which encodes a bHLH-PAS transcription factor, controls early development of the CNS midline cells (Nambu et al, 1991) by acting as a transcriptional activator that promotes the midline transcriptional program (Nambu et al, 1990) and indirectly represses the lateral CNS program (Estes et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have promoted a model in which sim initially commits ectodermal cells to a single midline neuronal precursor fate followed by a series of signaling events that further diversify midline cell fates (Watson and Crews, 2012). During midline cell differentiation, sim continues to control transcription in midline glia (MG) (Estes et al, 2008; Wharton et al, 1994) and may interact with the Notch signaling pathway, another important regulator of MG transcription and development (Wheeler et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…More detailed analysis of the FlyLight Gal4 lines revealed that all three fragments drive expression in distinct posterior midline subsets of the endogenous en/inv pattern (Fig. S1), which is likely to reflect the complexities of en/inv midline function (Watson et al, 2011;Watson and Crews, 2012;Wheeler et al, 2006). Subsequently, the publication of the Fly Enhancer database (Kvon et al, 2014) (Fig.…”
Section: Faire Identifies Multiple New Midline Enhancers In the Engramentioning
confidence: 95%
“…Drosophila CNS midline cells provide a useful experimental system for studying transcriptional regulation during CNS development. The development of the midline neurons and glia is well characterized with regards to both cellular and molecular mechanisms (Watson et al, 2011;Watson and Crews, 2012;Wheeler et al, 2008). Multiple large-scale screens have identified hundreds of genes that are expressed in midline cells (along with associated enhancers), and several transcription factors are known that control midline cell transcription (Kearney et al, 2004;Kvon et al, 2014;Manning et al, 2012;Tomancak et al, 2002Tomancak et al, , 2007Wheeler et al, 2006Wheeler et al, , 2009.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation